Study of the boomerang effect in a digital community among young people: Synergies and differences between advertising communication and museum experience - Pedreño-Santos, Ana; Carcelén Garcia, Sonia; Viñarás Abad, Mónica (Street Art & Urban Creativity, 2025)
This research proposes an exploratory work, through the search for new proposals to raise awareness of high-impact social issues, based on the potential of the museum experience as a persuasive communication tool. The purpose of the study is to compare the boomerang effect through the impact that can be caused by a traditional advertising communication and a museum experience. The work has been designed with a qualitative and experimental methodology through a Digital Community with a sample of young people divided into two groups and exposed to two different stimuli: a spot and a visit to the museum, working in both cases under the same social content, such as their attitude towards racism. The results show differences in the groups depending on the way in which they have been exposed to and consumed the content, which opens a way to investigate new alternatives in persuasive communication.